Hypermobility Assessment in 1, 004 Adult Patients Presenting with Hip Pain: Correlation with Diagnoses and Demographics. (4th November 2020) - Santore, R.F.; Gosey, G.M.; Muldoon, M.P.; Long, A.A.; Healey, R.M.
Abstract : Background: The strength of the association between hypermobility and developmental dysplasia of the hip (DDH) in adults is unknown. We sought to analyze this relationship in a prospective, blinded, institutional review board-approved, observational study. The hypothesis was that the prevalence of generalized joint hypermobility (GJH) would be significantly higher in patients with hip dysplasia than in those with other hip diagnoses on the basis of clinical observations of joint laxity. Methods: One thousand and four consecutive new patients (390 males and 614 females) seen over a 4-year period were evaluated for hypermobility of the hip using 2 criteria: the Beighton 9-point physical examination criteria and the Hakim-Grahame 5-item history questionnaire. Diagnosis, age, sex, and race were tested as predictors of hypermobility. Patient-reported outcome scores from the International Hip Outcome Tool (iHOT-12) and the modified Harris hip score (mHHS) were also assessed. Results: DDH was the primary diagnosis in 33.2% of the patient population. Patients who had dysplasia without osteoarthritis (OA) had a significantly elevated prevalence of GJH (77.9%) compared with those with nondysplastic hips (32.8%; p < 0.0001) or with patients who had dysplasia and OA (35.7%; p < 0.0001) according to either method. The odds ratio (OR) for patients with DDH versus those with other diagnoses was 7.1 (95% confidence interval [CI]: 5.1 to 10.0). The prevalence of hypermobility was significantly greater in females than in males (OR = 4.2 [95% CI: 3.2 to 5.5]; p < 0.0001). The prevalence of GJH was inversely proportional to age. There was a significantly reduced prevalence of GJH observed in Hispanic patients (p < 0.05) compared with other races. GJH was not a predictor of patient-reported outcome scores (p = 0.51 for iHOT-12 and p = 0.44 for mHHS). Conclusions: To our knowledge, this study is the first to establish a strong association between hypermobility and DDH in adults, confirming the hypothesis. We recommend utilizing both the Beighton and Hakim-Grahame scoring systems together as routine components of the history and physical examination for patients with hip dysplasia. Further research is warranted to explore the genetic basis and potential causal relationships between soft-tissue laxity and skeletal dysplasia, as well as improvements in assessment tools. Level of Evidence: Prognostic Level II . See Instructions for Authors for a complete description of levels of evidence.